Hubungan Karakteristik dengan Sikap Peternak terhadap Usaha Peternakan Sapi Perah di Kabupaten Wonosobo - Paramandita, Helmi; Muatip, Krismiwati; Purwaningsih, Hermin (ANGON: Journal of Animal Science and Technology, 2019)
Background. The study aimed to determine the characteristics and attitudes of dairy farmers in Wonosobo District and analyze the relationship between characteristics and attitudes of dairy farmers in Wonosobo District. Material and methods. The research method used is the survey method. Determination of regional samples is carried out by purposive sampling method, which is to take sub-districts that have dairy farmers in Wonosobo Regency and are elected. Respondents were taken by the census method, namely that all farmers in the subdistrict were selected. The total number of respondents was 35 people. The analysis used is Descriptive Analysis and Spearman Rank Correlation. Results. The results showed that the level of education of farmers in Wonosobo District in the category was quite high, the length of raising in the new category (7 years) and the number of livestock owned in the low category. The attitude of farmers to the price of milk and the price of concentrates has an opinion quite agree with the low price of milk and high concentrated prices, the attitude of farmers to the role of groups having group opinions is not useful. The results of the Spearman rank analysis showed that there was a significant relationship between the education of breeders and the length of breeding with the attitude of farmers with a correlation coefficient of 0.447 and 0.429. There is no relationship between the number of livestock with the attitude of farmers with a correlation coefficient of - 0.027. Conclusion.